In Vitro Antibacterial Activity of Genistein and Quercetin against Escherichia Coli Isolated from Clinical Samples - Berakdar, Noura (Innovare Journal of Life Sciences, 2016)
In this work: the aim of this study was to investigate the antibacterial activity of Genistein and Quercetin against pathogens of the urinary tract infection. An in vitro study was carried out using the following bacterial strains involved in UTI diseases by using well diffusion testing (WD): E. coli (ATCC 25922) and 10 strains were compiled from Aleppo Hospital. It were from women and men have urinary tract infection (UTI). The antibacterial activity of Genistein and Quercetin was determined in form of inhibition zone using agar well diffusion testing. In all experiments, results obtained indicated that Genistein and Quercetin had inhibitory effects on E. coli (ATCC 25922) and some 10 strains. The present study showed that Genistein and Quercetin were active against the tested bacterial strains, in which the Genistein showed better antibacterial effect the tested bacterial strains. The Genistein and Quercetin could be encouraged for further development in caries prevention and treatment. . Â 